HGF and SDF‐1‐mediated mobilization of CD133+BMSC for hepatic regeneration following extensive liver resection. Issue 1 (23rd May 2013) - Lehwald, Nadja; Duhme, Constanze; Wildner, Marina; Kuhn, Stephanie; Fürst, Günter; Forbes, Stuart J.; Jonas, Sven; Robson, Simon C.; Knoefel, Wolfram T.; Schmelzle, Moritz; Schulte am Esch, Jan
Abstract Background The molecular mechanisms of haematopoietic stem cells (HSC) mobilization and homing to the liver after partial hepatectomy (PH) remain largely unexplored. Methods Functional liver volume loss and regain was determined by computerized tomography (CT) volumetry in 30 patients following PH. Peripheral HSC mobilization was investigated by fluorescence‐activated cell sorting (FACS) analyses and cytokine enzyme‐linked immunosorbent assay assays. Migration of purified HSC towards hepatic growth factor (HGF) and stroma‐derived factor‐1 (SDF‐1) gradients was tested in vitro. Mice after 70% PH were examined for HSC mobilization by FACS and cytokine mRNA expression in the liver. FACS‐sorted HSC were administered after PH and hepatocyte proliferation was evaluated by immunohistochemical staining for Ki67. Results Impaired liver function was noted after extended hepatic resection when compared to smaller resections. Patients with large liver resections were characterized by significantly higher levels of peripheral HSC which were positively correlated with the extent of resected liver volume and its regain after 3 weeks. Increased plasma levels of HGF, SDF‐1 and insulin like growth factor (IGF‐1) were evident within the first 6 hours post resection. Migration assays of human HSC in vitro showed a specific target‐demonstrated migration towards recombinant HGF and SDF‐1 gradients in a concentration and specific receptor (c‐Met and CXCR4) dependent manner. The evaluation of peripheral human alpha foetoprotein expression demonstrated pronounced stemness following increased CD133+HSC in the course of liver regeneration following PH. Our human data were further validated in a murine model of PH and furthermore demonstrated increased hepatocyte proliferation subsequent to CD133+HSC treatment. Conclusion HGF and SDF‐1 are required for effective HSC mobilization and homing to the liver after hepatic resection. These findings have significant implications for potential therapeutic strategies targeting chemotactant modulation and stem cell mobilization for liver protection and regeneration.